2017
DOI: 10.1007/s00221-017-5008-2
|View full text |Cite
|
Sign up to set email alerts
|

Action ability modulates time-to-collision judgments

Abstract: Time-to-collision (TTC) underestimation has been interpreted as an adaptive response that allows observers to have more time to engage in a defensive behaviour. This bias seems, therefore, strongly linked to action preparation. There is evidence that the observer’s physical fitness modulates the underestimation effect so that people who need more time to react (i.e. those with less physical fitness) show a stronger underestimation effect. Here we investigated whether this bias is influenced by the momentary ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 88 publications
4
18
0
1
Order By: Relevance
“…Participants erroneously predicted a collision even though it was not physically possible. Because it is particularly difficult to keep track of moving stimuli following different velocities (Pylyshyn, 2004 ; Fencsik et al, 2007 ), one interpretation of these findings was that anticipating even erroneously collision event would provide an adaptive advantage by ensuring that individuals are allowed to prepare for appropriate behavior (Neuhoff, 1998 , 2001 ; Vagnoni et al, 2017 ). The specific way spatio-temporal information is processed may thus reflect the motor, anticipatory and adaptive function of the PPS that works like an alert system for timely preparing reactions to events that occur near the body (Coello and Iachini, 2020 ).…”
Section: The Enhanced Perceptual and Cognitive Processing In The Ppsmentioning
confidence: 99%
“…Participants erroneously predicted a collision even though it was not physically possible. Because it is particularly difficult to keep track of moving stimuli following different velocities (Pylyshyn, 2004 ; Fencsik et al, 2007 ), one interpretation of these findings was that anticipating even erroneously collision event would provide an adaptive advantage by ensuring that individuals are allowed to prepare for appropriate behavior (Neuhoff, 1998 , 2001 ; Vagnoni et al, 2017 ). The specific way spatio-temporal information is processed may thus reflect the motor, anticipatory and adaptive function of the PPS that works like an alert system for timely preparing reactions to events that occur near the body (Coello and Iachini, 2020 ).…”
Section: The Enhanced Perceptual and Cognitive Processing In The Ppsmentioning
confidence: 99%
“…Interestingly, looming stimuli which are explicitly threatening are perceived as having a shorter time-to-impact latency in comparison to objects moving at the same objective speed and which are not threatening ( Vagnoni et al, 2012 ). This underestimation of approaching stimuli is also influenced by ones motor abilities, and is for example increased if subjects have their heads constrained by a chin rest compared to when standing freely ( Vagnoni et al, 2017 ), the former condition possibly indicating, due to the constraint, an increased threat relative to the unconstrained condition. The neuronal underlying of this observation is to our knowledge, completely unexplored.…”
Section: Looming Stimuli and Touch Or Impact Prediction To The Bodymentioning
confidence: 99%
“…Like PPS representations that support non‐defensive behaviors, there is evidence that representations of PPS are flexible in defensive contexts. For example, Vagnoni, Andreanidou, Lourenco, and Longo (), Vagnoni, Lourenco, and Longo (), Vagnoni, Lourenco, and Longo () have reported that looming images of threatening stimuli (i.e., snakes and spiders) were judged as arriving sooner than nonthreatening stimuli (i.e., rabbits and butterflies) on a time‐to‐contact (TTC) task. One interpretation is that this effect could result from participants experiencing larger representations of PPS in the presence of evolutionary threatening animals as compared to nonthreatening animals, leading them to judge the former as making contact with themselves sooner.…”
Section: The Defensive Functionmentioning
confidence: 99%